Phylogenomics and Historical Biogeography of Seahorses, Dragonets, Goatfishes, and Allies (Teleostei: Syngnatharia): Assessing Factors Driving Uncertainty in Biogeographic Inferences. (23rd April 2021) - Santaquiteria, Aintzane; Siqueira, Alexandre C; Duarte-Ribeiro, Emanuell; Carnevale, Giorgio; White, William T; Pogonoski, John J; Baldwin, Carole C; Ortí, Guillermo; Arcila, Dahiana; Ricardo, Betancur-R
Abstract: The charismatic trumpetfishes, goatfishes, dragonets, flying gurnards, seahorses, and pipefishes encompass a recently defined yet extraordinarily diverse clade of percomorph fishes—the series Syngnatharia. This group is widely distributed in tropical and warm-temperate regions, with a great proportion of its extant diversity occurring in the Indo-Pacific. Because most syngnatharians feature long-range dispersal capabilities, tracing their biogeographic origins is challenging. Here, we applied an integrative phylogenomic approach to elucidate the evolutionary biogeography of syngnatharians. We built upon a recently published phylogenomic study that examined ultraconserved elements by adding 62 species (total 169 species) and one family (Draconettidae), to cover ca. 25% of the species diversity and all 10 families in the group. We inferred a set of time-calibrated trees and conducted ancestral range estimations. We also examined the sensitivity of these analyses to phylogenetic uncertainty (estimated from multiple genomic subsets), area delimitation, and biogeographic models that include or exclude the jump-dispersal parameter (j) . Of the three factors examined, we found that the j parameter has the strongest effect in ancestral range estimates, followed by number of areas defined, and tree topology and divergence times. After accounting for these uncertainties, our results reveal that syngnatharians originated in the ancient Tethys Sea ca. 87 Ma (84–94 Ma; Late Cretaceous) and subsequently occupied the Indo-Pacific. Throughout syngnatharian history, multiple independent lineages colonized the eastern Pacific (6–8 times) and the Atlantic (6–14 times) from their center of origin, with most events taking place following an east-to-west route prior to the closure of the Tethys Seaway ca. 12–18 Ma. Ultimately, our study highlights the importance of accounting for different factors generating uncertainty in macroevolutionary and biogeographic inferences.[Historical biogeography; jump-dispersal parameter; macroevolutionary uncertainty; marine fishes; syngnathiformes; ultraconserved elements].